Streamlining the Procurement Lifecycle: An Integrated Web-Based Platform for PPMP Consolidation and Document Tracking - Rommel S. Pabustan; Alaina Thea V. Concepcion (Future Science / FSH-PH Publications, 2026)
The research dealt with the impracticality of the manual administrative procedure, as they came up with a research titled;